ANALISIS STRUKTUR MIKRO TERHADAP HASIL EKPERIMENTAL SAMBUNGAN LAS SMAW PADA BAJA KARBON ST 37 - Okviyanto, Toni; Dibyo Setiawan; Gugun Nugraha; Sutrimo; Destri Muliastri (Politeknik Negeri Sriwijaya, Indonesia, 2023)
Welding is a process of joining two or more metals using thermal energy to melt them. The thermal processes of welded joints affect the phase change and the physical, microstructural, and mechanical properties of the weld. The purpose of the activity, to analyze the results of SMAW welded joints, parameters of current strength, and seam angle of the ST 37 carbon steel microstructure is a continuation of previous publication activities. Variation of the current strength of 90 A, 100 A, 110 A and seam angles of 600 and 700 with electrodes Ã˜2.6 mm and Ã˜3.2 mm. During the welding process, a series of thermal cycles of the weld metal and HAZ occur, from thermalization to maximum temperature and then undergoing a cooling process. The final composition of the weld metal, filler metal, and the condition of the air in the weld area are factors for the formation of the microstructure. Microstructures such as acicular ferrite can improve the mechanical properties of the weld metal. Visualization of the microstructure using an optical microscope during the metallographic inspection process was carried out by observing the grain size and phase formed on the base metal, heat-affected zone (HAZ), fusion line (FL), and weld metal (WL). The results showed that the weld metal (WM) with a series of experiments tended to have a larger acicular ferrite structure. The conclusion of the microstructural analysis is that the greater the current strength and seam angle, the more acicular ferrite structures are formed.